A prospective, open label, randomized-controlled study to evaluate the efficacy and safety of MyVir tablets in mildly symptomatic COVID-19 patients - Jayanthi, C. R.; S., Shankar A.; Shankar, M. Ravi; S. P. T., Lakshmana Perumal; L., Manjunath Reddy; K., Renish T. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Coronavirus can cause pneumonia, respiratory failure and death. The emergence of novel coronavirus has posed a challenging situation that warrants urgent global attention. Currently there was no effective therapy available for COVID-19 and hence antiviral and immune modulators are most sought after medicines to manage complications of COVID-19. Methods: In this study involving mild COVID-19 we randomized 42 patients to receive a MyVir tablets twice daily along with standard of care (SOC) or SOC alone in 1:1 ratio for 14 days. We evaluated the benefits of MyVir tablets by assessing clinical outcomes and improvement in immune markers (LDH, CRP, D-dimer, TLC). Results: At the end of the study the immune markers in MyVir group improved significantly compared to control group. In patients who received MyVir, CRP decreased from 3.3 mg/l to 1.7 mg/l (p=0.0171). D-dimer decreased from 0.589 on day 0 to 0.368 on day 14 (p=0.03) and LDH decreased from 224 U/l on day 0 to 158 U/l on day 14 in test group (p=0.05). TLC showed favorable improvement in study group compared to control group. Early recovery from COVID-19 symptoms was observed in patients on MyVir treated group. Patients treated with MyVir tablets reduced the duration of hospitalization when given along with standard of care. Conclusions: MyVir accelerated recovery of COVID-19 patients by early improvement in clinical symptoms and immune markers in this study and results clearly indicates that MyVir tablets has antiviral, immune booster activity. Hence this study provides evidence that MyVir has definitive role in the management of mild COVID-19 patients along with standard of care (funded by Mi Lab Life Sciences(P) Ltd. CTRI no. CTRI/2020/05/024967).